95 A rare case of Lactobacillus Plantarum prosthetic valve endocarditis. (17th January 2020) - Tavernese, A; Caldara, F; Muscoli, S; Stelitano, M; Uccello, G; Mauceri, A; Mollace, R; Sordillo, P; Andreoni, M; Romeo, F; Cammalleri, V
Abstract: INTRODUCTION: Lactobacillus species are rare human pathogens but have been implicated in a variety of infections, including bacteremia and endocarditis, with Lactobacillus casei and Lactobacillus rhamnosus among the most frequently isolated species. Endocarditis due to Lactobacillus represents <0.5% of all cases of endocarditis and are associated with structural heart diseases, recent surgery, extended antibiotic and probiotic use and immuno-deficiency. We report a case of Lactobacillus plantarumendocarditis in a patient with biological aortic prosthetic valve. CASE REPORT: Our patient is a 48 year-old male with a past medical history of surgical aortic replacement with a biological prosthetic valve in 2013. He reports the onset of symptoms 4 months before with worsening asthenia. The patient presented to a cardiologist after 3 months from symptoms beginning. A transesophageal echocardiogram (TEE) described marked fibro-plastic thickening of the cusps with two elongated vegetations (12 mm and 7 mm) causing a moderate-to-severe aortic steno-regurgitation. A few days later he came to our emergency department. On admission, the patient was afebrile, eupnoeic on room air. The cardiac examination revealed a regular rate and rhythm with a grade 4 of 6 holosystolic murmur loudest at the aortic and pulmonary focus. Three sets of blood cultures were drawn on admission. Hence, he was transferred to the Infectious Diseases Department where he started antibiotic therapy with Ceftriaxone and Gentamicin. A 18F-FDG PET-CT total body showed tracer accumulation close to the prosthetic aortic valve. Few days later Lactobacillus Plantarum was isolated from blood cultures and, according to the antibiogram results, therapy was adjusted using G Penicillin, Vancomicyn and Gentamicin. The TEE, performed during the hospitalization, showed one mobile vegetation, reduced in size (5 mm), adherent to the anterior aortic cusp, which prolapsed in the left ventricular outflow tract and commissural fusion, causing severe steno-regurgitation (Gmax 84 mmHg, Gmed 54 mmHg). During hospitalization the serial blood cultures resulted negative. Serial TEEs were also performed (3rdand 6thweek), showing a gradual reduction of the cusps thickening and disappearance of commissural fusion (Figure). In the last TEE no vegetations were described, and the transaortic mean gradient was reduced (Gmed 38 mmHg), persisting severe regurgitation. Hence the patient was discharged with oral antibiotic therapy (amoxicillin and clavulanic acid) and indication to redo aortic valve surgery. Written informed consent was obtained. CONCLUSIONS: L. plantarum is a rare form of endocarditis. In our patient it caused fibro-plastic thickening of the bioprosthesis cusps and commissural fusion, determining severe steno-regurgitation. It also responded to targeted antibiotic therapy with improvement in cusp mobility but persistence of severe regurgitation.